Adoption and diffusion of blockchain technology - Christoph Gschnaidtner; Robert Dehghan; Hanna Hottenrott; Julian Schwierzy (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
A widespread approach to measuring the innovative capacity of companies, sectors, and regions is the analysis of patents and trademarks or the use of surveys. In emerging digital technologies this approach may, however, not be sufficient for mapping technology diffusion. This applies to blockchain technology which is in essence, a decentralized and distributed database (management system) that is increasingly used well beyond its originally intended purpose as the underlying infrastructure for a peer-to-peer payment system. In this article, we use an alternative method based on web-analysis and deep learning techniques that allow us to identify companies that use blockchain technology to determine its diffusion. Our analysis shows that blockchain is still a niche technology with only 0.88% of the analyzed firms using it. At the same time, certain sectors, namely ICT, banking & finance, and (management) consulting, show higher adoption rates ranging from 3.50% to 4.50%. Most blockchain companies are located at or close to one of the financial centers. Young firms whose business model is (partly) based on blockchain technology also locate themselves close to these centers. Thus, despite blockchain technology often being explicitly characterized as decentralized and distributed in nature, these adoption and strategic location decisions lead to "blockchain clusters".
Keywords: C45; O33; R30; 330; technology adoption; blockchain technology; geographical distribution of firms; natural language programming